REKONSTRUKSI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERWAWASAN HAM - Kasinyo Harto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This working paper discusses the need for human rights insight in the learning of Islamic religious education. The emergence of many violations of human rights values, such as the case of conflict among students, bullying disturbance, conflicts and violence, and so forth, is a shining example of powerlessness of an educational system in this country, specifically Islamic religious education. It is sure that there is something wrong in procedure and mechanism of religious education. After analyzing it in depth, author designed a systemic methodology of teaching of Islamic religious education with human rights insist.